Gender Bias: The Role of Women and Gender Equality in Education - Fitriyani Fitriyani; Arifin Maksum; Nina Nurhasanah (International Journal of Science and Applied Science: Conference Series, 2022)
Gender equality in modern society today is still hindered by stereotypes regarding the roles and positions of men and women. Gender is a view or belief formed by society about how a woman or man should behave or think. In society the role of life is dominated more by the role of men and in public life under their authority is women. In the Qur'an surah Al-Isra verse 70 which reads that Allah Almighty has created human beings ie men and women in the best form with the most honorable position. The method that will be used is to use a quality approach to be able to obtain data on the benefits of gender relations in Islam more than just regulating gender justice in society, but theologically regulating the pattern of microcosm (human), macrosrosmos (nature) , and God relations. Islam came to give an important position in both the law and the same rights as men, so that there is no discrimination for women. The problem that exists today is that there are differences in views on the position and perspective of women in the educational environment where there are some opinions that say that Women are very dependent on men, so that currently the issue of women leaders in the world of education provides a complete picture of their position, political rights, professional employment opportunities have nothing to do with religious values, only there are still differences between scholars, community leaders and the community itself[1], this finally proves that there is no gender bias in the world of education.